KRITIK TERHADAP REKONSTRUKSI METODE PEMAHAMAN HADIS MUHAMMAD AL-GHAZALI - Sri Purwaningsih (Jurnal Theologia, 2017)
Abstract: Muhammad al-Ghazali is a controversial figure. Some give a positive appreciation to the method of hadith understanding he offered and regarded as a solutive method at the present day. But, other accused him as inkar al-sunnah and regarded his method was inapplicable. According to the author, some ideas of the reconstruction on the method of hadith understanding of Muhammad al-Ghazali still use a positivist paradigm that focuses on objectivity, while there are no objects without a subject. Therefore, in this paper, the author emphasizes the discussion on two points; first, criticizing the application of the method of hadith understanding of Muhammad al-Ghazali; and second, offering the new method of reconstruction using descriptive analysis and explanation method. The author examines the book of Muhammad al-Ghazali and other books that are the result of criticism of the researchers about him. The result, studying and understanding the hadiths requires a set of batiniyah in the form of consciousness and sincere intention, studying the authenticity of the hadith, structural and pragmatic analysis, and the reviewer must verify the results of intellectual activity comprehensively.Abstrak: Muhammad al-Ghazali merupakan tokoh kontroversial. Ada yang memberikan apresiasi positif atas metode pemahaman hadis yang ditawarkannya yang dianggap solutif pada saat sekarang. Namun ada juga yang menuduhnya sebagai inkar al-sunnah dan menilai metode yang ditawarkannya belum aplikatif. Menurut penulis, beberapa tawaran rekonstruksi terhadap metode pemahaman hadis Muhammad al-Ghazali masih menggunakan paradigma positivisme yang menitikberatkan pada objektivitas, padahal tidak ada objek tanpa subjek. Dalam tulisan ini, penulis menekankan dua pembahasan, yakni: mengkritik aplikasi metode pemahaman hadis Muhammad al-Ghazali; dan menawarkan bentuk rekonstruksi metode yang baru dengan menggunakan metode analisis deskriptif dan penjelasan. Penulis mengkaji buku karya Muhammad al-Ghazali dan buku-buku lain yang merupakan hasil kritikan para peneliti terhadapnya. Hasilnya, di dalam mengkaji dan memahami hadis diperlukan seperangkat batiniyah berupa kesadaran dan niat yang ikhlas, mengkaji otentisitas hadis, analisis struktural dan pragmatik, dan pengkaji melakukan verifikasi terhadap hasil aktifitas intelektual (pemahaman) secara komprehensif.